Physiological and structural tradeoffs underlying the leaf economics spectrum. Issue 4 (10th March 2017) - Onoda, Yusuke; Wright, Ian J.; Evans, John R.; Hikosaka, Kouki; Kitajima, Kaoru; Niinemets, Ülo; Poorter, Hendrik; Tosens, Tiina; Westoby, Mark
Summary: The leaf economics spectrum (LES) represents a suite of intercorrelated leaf traits concerning construction costs per unit leaf area, nutrient concentrations, and rates of carbon fixation and tissue turnover. Although broad trade‐offs among leaf structural and physiological traits have been demonstrated, we still do not have a comprehensive view of the fundamental constraints underlying the LES trade‐offs. Here, we investigated physiological and structural mechanisms underpinning the LES by analysing a novel data compilation incorporating rarely considered traits such as the dry mass fraction in cell walls, nitrogen allocation, mesophyll CO2 diffusion and associated anatomical traits for hundreds of species covering major growth forms. The analysis demonstrates that cell wall constituents are major components of leaf dry mass (18–70%), especially in leaves with high leaf mass per unit area (LMA) and long lifespan. A greater fraction of leaf mass in cell walls is typically associated with a lower fraction of leaf nitrogen (N) invested in photosynthetic proteins; and lower within‐leaf CO2 diffusion rates, as a result of thicker mesophyll cell walls. The costs associated with greater investments in cell walls underpin the LES: long leaf lifespans are achieved via higher LMA and in turn by higher cell wall mass fraction, but this inevitably reduces the efficiency of photosynthesis. Abstract : See also the Commentary on this article by Reich & Flores‐Moreno, 214 : 1395–1397 .